2022
DOI: 10.5334/gh.1101
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Mortality During the COVID-19 Pandemics in a Large Brazilian City: A Comprehensive Analysis

Abstract: Introduction:The impact of COVID-19 pandemics on cardiovascular diseases (CVD) may be caused by health system reorganization and/or collapse, or from changes in the behaviour of individuals. In Brazil, municipalities were empowered to define regulatory measures, potentially resulting in diverse effects on CVD morbimortality.Objective: To analyse the impact of COVID-19 pandemics on CVD outcomes in Belo Horizonte (BH), the sixth greater capital city in Brazil, including: mortality, mortality at home, hospitaliza… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
1
5
0
3
Order By: Relevance
“…Primarily, a significant increase in total deaths due to CVD was observed during the pandemic period, with 19,376 deaths recorded compared to 8,821 deaths in the pre-pandemic period. Previous reports ( 6 , 23 29 ) support our findings and indicate that CVD is a primary mortality factor in COVID-19 patients. These outcomes imply an association between the pandemic and increased CVD-related deaths, potentially attributed to factors such as limited access to medical care ( 6 ), treatment postponements ( 7 ), pre-existing CVD ( 8 , 26 ), and the impact of pandemic-related stress.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Primarily, a significant increase in total deaths due to CVD was observed during the pandemic period, with 19,376 deaths recorded compared to 8,821 deaths in the pre-pandemic period. Previous reports ( 6 , 23 29 ) support our findings and indicate that CVD is a primary mortality factor in COVID-19 patients. These outcomes imply an association between the pandemic and increased CVD-related deaths, potentially attributed to factors such as limited access to medical care ( 6 ), treatment postponements ( 7 ), pre-existing CVD ( 8 , 26 ), and the impact of pandemic-related stress.…”
Section: Discussionsupporting
confidence: 91%
“…However, it is essential to note that CVD rates within hospitalizations exhibited a relative decrease, suggesting a considerable number of deaths occurred outside of hospitals, such as in homes or clinics ( 24 ). For instance, in socially vulnerable cities like Belo Horizonte in Brazil, higher rates of non-hospital deaths were observed ( 29 ). This phenomenon can be attributed to significant shifts in healthcare delivery induced by the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…IC 95%, 0,75-0,84) e mortes hospitalares (RR 0,76; IC 95%, 0,57-1,01) por SCA, além de aumento nos óbitos domiciliares (RR 1,38; IC 95%, 1,04-1,82) 66. • Em estudo de série temporal em Belo Horizonte, o número de hospitalizações por SCA no período pandêmico de 2020 foi 21% menor do que o projetado (n=2.369 e 3.013, respectivamente).142• As admissões por eventos coronarianos urgentes e eletivos entre 18 de março e 30 de setembro de 2020 foram comparadas às hospitalizações durante uma série histórica de dois anos (2018 e 2019) no contexto do plano de saúde UNIMED-BH, um sistema médico privado que cobre aproximadamente 1,31 milhão de indivíduos (22% da população) na área metropolitana de Belo Horizonte.…”
unclassified
“…[4][5][6][7][8][9][10] Importantly, a repeatedly reported finding is an uncomfortable increase in home deaths. [11][12][13] Therefore, it is now clear that the pandemic has substantially impacted CVD care in Brazil.…”
mentioning
confidence: 99%
“…15 Also, Brant et al reported that the increase in CVD home deaths in Belo Horizonte-MG in 2020 was more pronounced in more socially vulnerable individuals. 13 Identifying the most affected subgroups is strategic for defining priority targets for public health interventions and avoiding the dangerous path of increasing health inequalities.…”
mentioning
confidence: 99%